PENGARUH TEKNIK SINTESIS TERHADAP KUALITAS PRODUK FATTYAMINA SEKUNDER - Komar Sutriah; Zainal Alim Mas'ud; Tun Tedja Irawadi (Research Center for Chemistry - LIPI, 2011)
Secondary fattyamines has been synthesized by reacting primary fatty amines with acylchlorides and continued with reducing the corresponding secondary fattyamides formed to secondary fattyamines using LiAIH<I'Fatty amines are raw material of natural-based surfactants that can be derived from fatty acids, olefins, or alcohols, of which can be synthesized from natural sources such as palm oil. Conversion of secondary fatty amides to secondary fatty amines was evaluated through the quality of FTIR spectra on wave number of 1639-1645 em' (C=O vibration) and 1544-1555 em